Pembuatan Mesin Penyuir Ikan Sistem Rotary Untuk Produk Abon Ikan: Manufacture of Rotary Fish Shredder Machine For Shredded Fish Products - Arinal Hamni (Universitas Muhammadiyah PROF. DR. HAMKA Fakultas Teknik – Program Studi Teknik Mesin, 2022)
Fish meat shredder machine is used to increase the added value of the product, so that the selling price of products produced from fish raw materials increases and is profitable for fishermen on the Tanggamus coast. Making a fish meat shredding machine begins with designing using solid work and making technical drawings with details. The manufacture is carried out and then assembling and testing the performance of the shredder machine. The test results show that the shredder machine has been successfully made with a production capacity of up to 2 kg in 15 minutes. The whistling time of 15 minutes resulted in small and relatively uniform shreds of fish meat. Thus, the test results of the shredder machine can produce better cuts of meat and in a relatively short time.